2023
DOI: 10.3389/frdem.2023.1303256
|View full text |Cite
|
Sign up to set email alerts
|

Elevated gonadotropin levels are associated with increased biomarker risk of Alzheimer's disease in midlife women

Matilde Nerattini,
Federica Rubino,
Steven Jett
et al.

Abstract: IntroductionIn preclinical studies, menopausal elevations in pituitary gonadotropins, follicle-stimulating hormone (FSH) and luteinizing hormone (LH), trigger Alzheimer's disease (AD) pathology and synaptic loss in female animals. Herein, we took a translational approach to test whether gonadotropin elevations are linked to AD pathophysiology in women.MethodsWe examined 191 women ages 40–65 years, carrying risk factors for late-onset AD, including 45 premenopausal, 67 perimenopausal, and 79 postmenopausal part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…We have shown that MS-Hu6 has an acceptable a nity to FSH, with a K D of 7.2 nM that approaches trastuzumab; a long half-life of 7.8 days in humanized Tg32 mice; limited, but measurable accumulation in the brain upon subcutaneous injection; and thermal, colloidal, monomeric, structural and accelerated stability in formulation, as evidence of durability and manufacturability 30,41,42 . However, supporting our core concept of inhibiting FSH to prevent MCI is a recent study in women between ages 40 to 65, of which 35% were perimenopausal--documenting a strong positive correlation between serum FSH levels and Aβ load (measured on PET scans) and gray matter volume in AD-vulnerable regions 43 .…”
Section: Discussionmentioning
confidence: 70%
“…We have shown that MS-Hu6 has an acceptable a nity to FSH, with a K D of 7.2 nM that approaches trastuzumab; a long half-life of 7.8 days in humanized Tg32 mice; limited, but measurable accumulation in the brain upon subcutaneous injection; and thermal, colloidal, monomeric, structural and accelerated stability in formulation, as evidence of durability and manufacturability 30,41,42 . However, supporting our core concept of inhibiting FSH to prevent MCI is a recent study in women between ages 40 to 65, of which 35% were perimenopausal--documenting a strong positive correlation between serum FSH levels and Aβ load (measured on PET scans) and gray matter volume in AD-vulnerable regions 43 .…”
Section: Discussionmentioning
confidence: 70%
“…We have shown that MS-Hu6 has an acceptable affinity to FSH, with a K D of 7.2 nM that approaches trastuzumab; a long half-life of 7.8 days in humanized Tg32 mice; limited, but measurable accumulation in the brain upon subcutaneous injection; and thermal, colloidal, monomeric, structural and accelerated stability in formulation, as evidence of durability and manufacturability 30,41,42 . However, supporting our core concept of inhibiting FSH to prevent MCI is a recent study in women between ages 40 to 65, of which 35% were peri-menopausal--documenting a strong positive correlation between serum FSH levels and Aβ load (measured on PET scans) and gray matter volume in AD-vulnerable regions 43 .…”
Section: Discussionmentioning
confidence: 71%